2022
DOI: 10.1177/00031348221087395
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Analysis of the Use of Closed-Incision Negative Pressure System in Vascular Surgery Groin Incisions

Abstract: Objective Closed-incision negative pressure therapy (CINPT) with the Prevena system has been used and clinically evaluated in high-risk groin incisions to reduce the risk of postoperative complications. We performed a cost-effectiveness analysis evaluating CINPT in femoral-popliteal bypass with prosthetic graft. Methods A literature review looking at prospective randomized trials determined the probabilities and outcomes for femoral-popliteal bypass with and without CINPT. Reported utility scores were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…Additionally, the QALY difference demonstrated in our study is greater than that of the following published studies, respectively which both showed cost-effectiveness. 15,16 The favorable health effect was largely a result of the outcomes seen in Deharo et al . 9 where S3 was found to be associated with lower mortality, rehospitalization for heart failure, and pacemaker implantation, while stroke and noncardiovascular death was similar between groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the QALY difference demonstrated in our study is greater than that of the following published studies, respectively which both showed cost-effectiveness. 15,16 The favorable health effect was largely a result of the outcomes seen in Deharo et al . 9 where S3 was found to be associated with lower mortality, rehospitalization for heart failure, and pacemaker implantation, while stroke and noncardiovascular death was similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Still, this method may be more representative as it takes into account the patient perspective. Second, we utilized a validated visual analog scale to obtain utility scores, 15,16 adapted for interventional cardiology. Third, because this analysis utilized only outcomes evaluated in the Deharo study of over 31,000 patients, it did not include outcomes compared in other studies like paravalvular regurgitation, life-threatening bleeding, and other major vascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations